2017
DOI: 10.1007/s00167-017-4718-0
|View full text |Cite
|
Sign up to set email alerts
|

Bi-cruciate stabilized total knee arthroplasty can reduce the risk of knee instability associated with posterior tibial slope

Abstract: BCS TKA has a wide acceptable range of posterior tibial slope for avoiding knee instability if the posterior tibial slope is less than 10°. Surgeons should prioritize avoiding adverse effects over trying to achieve positive effects such as decreasing patellofemoral contact force and quadriceps force by increasing posterior tibial slope. Our study helps surgeons determine the optimal posterior tibial slope during surgery with BCS TKA; posterior tibial slope should not exceed 10° in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Anterior engagement was identified in 54.5% of knees in WB and 36.3% in NWB, indicating that the articular surface of the BCS‐TKA design could influence anterior stability. In a simulation study, Hada et al [12] reported an absence of anterior engagement with a PTS of < 6°. In this study, the average PTS was 3.4 ± 2.7°, and this small PTS angle likely explains the low occurrence of anterior engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior engagement was identified in 54.5% of knees in WB and 36.3% in NWB, indicating that the articular surface of the BCS‐TKA design could influence anterior stability. In a simulation study, Hada et al [12] reported an absence of anterior engagement with a PTS of < 6°. In this study, the average PTS was 3.4 ± 2.7°, and this small PTS angle likely explains the low occurrence of anterior engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, further studies 18,21,53,55 have reported continuous posterior translation due to increased tibial slopes. A higher posterior translation will lead to a greater lever arm of the quadriceps, which can be expected to improve motion efficiency, resulting in a reduced quadriceps force 21,24,53 . This can be explained with the resulting posterior force on the femur produced by an increased tibial slope and the gravity, thus locating the femur more posteriorly due to the ACL loss 58 .…”
Section: Discussionmentioning
confidence: 93%
“…In addition to intraoperative examinations, knee joint stability can be investigated using computational, experimental, or clinical studies. Although computational studies have shown great potential in clinical decision-making 11,12,17,18,21,38,45,48,53,54 , they are associated with uncertainties regarding the prediction of realistic contact conditions. On the other hand, experimental studies 16,24,26,34,36,55 lack the consideration of the complex soft tissue structures acting at the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…The computer simulation study has shown that anterior contact between the anterior aspect of the tibial post- and femoral component was observed if the posterior tibial slope was 6° or more. 25 Unlike VERASENSE system, compressive force of anterior cam and post can be measured in the current study and cases with less than 6° of the posterior inclination of tibia did not engage with anterior cam and post, therefore, we should aim for the patient’s physiological posterior inclination of tibia to substitute for ACL.…”
Section: Discussionmentioning
confidence: 93%